Top management teams and organizational renewal - Hurst, David; Rush, James C.; White, Roderick E. (Strategic Management Journal, 1989)
Increasingly the makeup of the top management group is believed to affect the development, identification and exploitation of strategic opportunities. This paper explains a creative management model, which goes beyond conventional strategic management, and identifies the behaviors of top managers needed for the ongoing renewal of their business. It is proposed these behaviors cluster and can be aligned with different and distinct cognitive styles or types. The implication is that top management groups should be composed of a mix of types. This paper posits a mix of Jungian types, Intuitives, Feelers, Thinkers and Sensors. This diversity can yield great strength if the differences can be focused and unified. Propositions and suggestions for further empirical research are developed.